The role of law in Chinese value chains - GAO, Henry (Institutional Knowledge at Singapore Management University, 2021)
Since starting its economic reform four decades ago, China has been highly successful in integrating its economy into regional and global value chains (GVCs). This started with simple assembly and processing, then expanded to low-end labor-intensive manufacturing, and gradually moved up to technology-intensive and capital-intensive industries. This article analyzes the development of Chinese law, legal institutions, and international and transnational legal initiatives to support the development of GVCs, which we divide into five phases. The article does not idealize law in terms of ‘commitment’ or ‘rule of law,’ but rather, in the legal realist tradition, views law as an important, contributing factor in economic change. It presents law as a signalling and coordinative device that serves to channel private conduct for business planning and coordination. The article provides insights for understanding current developments in the trading system and their implications for regional and global value chains.